THE EFFECT OF LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT. MEDCO E & P LEMATANG - Triviana, Dina; Idris, HM; Yamaly, Fadhil (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
This research aims to determine the effect of leadership and work environment on employee performance with job satisfaction as an intervening variable at PT Medco E & P Lematang. The variables used by researchers are the variables of Leadership, Work Environment, Job Satisfaction and Performance. The sample in this study was 124 employees at PT Medco E & P Lematang who were selected by cluster sampling. The data used in this study are primary data with questionnaire data collection methods. The data analysis technique used is Structural Modeling Equation (SEM) with the Lisrel Program Application. The results of this study indicate that: (1) Leadership has an insignificant effect on employee performance, (2) Work Environment has a positive and significant effect on employee performance, (3) Leadership has a positive and significant effect on employee job satisfaction, (4) work environment has a positive and significant effect on employee job satisfaction, (5) job satisfaction has a positive and significant effect on employee performance at PT. Medco E & P Lematang.